FORMATION OF THEORETICAL AND ORGANIZATIONAL-METHODICAL ASPECTS OF MANAGEMENT AUDIT - Karaev Payzillakhon Yusufxonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In article studied the problems of formation of the organization of theoretical and organizational and methodical aspects of administrative audit are studied. Are given the purpose and problems of administrative audit. It is opened ways of the account, the analysis of expenses and prime cost and production audit.